Kehadiran Negara Dalam Peningkatan Kualitas Pendidikan Di Indonesia Disanksikan Dapat Bersaing Dalam Asean Community - Budiharjo Budiharjo; Herry Rachmatsyah; Endang Sulastri (Universitas Prof. Dr. Moestopo (Beragama), 2017)
Establishment of the ASEAN Community will make every ASEAN countries will be involved in the global market . Education is a sector that is very important and strategic to improve the development of human resources in the face of the global market . In the ASEAN Community will occur free labor market in 2015 . Indonesia faced in education reform to produce competitive human resources at the regional level . The role of a strong state is needed to make Indonesia to compete in the ASEAN Community .